Strengthening the governance of free nutritious meals based on schools in Indonesia - K.P. Suharyono S.Hadiningrat; Teguh Yuwono; Novia Dwi Anggraeni (Yayasan Inspirasi Merah Putih Indonesia, 2025)
Efforts to improve the nation's intelligence and advance public welfare must be a commitment of the Indonesian people, and this must be realized through pro-people and sustainable government policies. Many challenges are faced, including preparing a healthy, intelligent generation with Pancasila character, to become a superior generation, especially in welcoming the Golden Indonesia Era in 2045. One such effort is the implementation of the Free Nutritious Meal Program (MBG), which is implemented by strengthening school-based governance. The hope is that this will accelerate services and equitable distribution of nutritional needs for communities throughout Indonesia. The challenge is not easy, requiring commitment from the central and regional governments to focus on and ensure the success of the MBG program. This research design is a qualitative descriptive study with a thematic narrative approach to identify and describe efforts to strengthen school-based MBG governance in Indonesia, where currently there is a gap in the role of schools limited to channeling MBG to SPPG and student beneficiaries. Through in-depth interviews with one of the BGN partner foundations, the SPPG, and schools in Tangerang City, qualitative data was obtained, which was then analyzed using a thematic narrative approach. The results showed that: a) the role of schools in the governance of the Free Nutritious Meal Program is currently limited to distributing MBG from SPPG to beneficiary students at their schools. Efforts to strengthen the governance of school-based Free Nutritious Meal Program must begin with a government commitment between BGN and the Ministry of Education, Culture, and Culture to collaborate with schools as SPPGs that serve MBG for their students, supported by the Ministry of Health.